Nawamin Siwasaranond: Exploring the Effects of Virtual Influencer Credibility Factors on Purchasing Decision Process for Fashion Products among Generation Z in Bangkok - Siwasaranond, Nawamin; Singlumpong, Ongart (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2024)
DOI: 10.14456/pnuhuso.2024.11 This research aims to 1) study the opinion level regarding trust factors of virtual influencers among Generation Z consumers in the Bangkok Province, 2) examine the opinion level regarding fashion purchasing decisions among Generation Z consumers in the Bangkok Province, and 3) investigate the relationship between opinions on trust factors of virtual influencers and opinions on fashion purchasing decisions among Generation Z consumers in the Bangkok Province using surveys as a data collection tool. The survey contents’ reliability and credibility were tested by using Cronbach's alpha with a sample of 30 participants, resulting in a confidence level of 0.62. Subsequently, 147 research participants were surveyed via questionnaire. Also, descriptive statistics and inferential statistic with Pearson's Product Moment Correlation Coefficient were employed to determine the relationship between independent and dependent variables. The research revealed that the opinions on trust factors of virtual influencers have a positive relationship with opinions on fashion purchasing decisions among Generation Z consumers in the Bangkok Province at the highest level (r = .829), with statistical significance of 0.01. Specifically, an increase in the credibility of virtual influencers significantly influences the fashion purchasing decisions of generation Z consumers. Generation Z consumers consider various factors related to the credibility of virtual influencer, namely trust, expertise, respect, similarity to the target audience, and attractiveness when making purchase decision about fashion products.